Please don't hurt me, I will rate you: Reputation systems as self-regulatory mechanisms for the sharing economy - Paraskevi (Vivian) M. Stergiou (Europa-Kolleg Hamburg, Institute for European Integration, 2020)
The rise of the sharing economy has generated great regulatory challenges. The European Union (EU) has to perform a fine balancing act. On the one hand, it has to safeguard weaker parties, consumers and workers, ensuring they enjoy fair treatment by adopting proper regulatory responses. On the other hand, since the sharing economy offers innovative solutions to common societal and consumer problems, the EU wishes to tap into its full potential. It is hard to strike the right balance between innovation and regulation. This paper contributes to the hot debate on how to regulate the sharing economy without stifling innovation, by examining reputation systems and their function as self-regulatory mechanisms. Can the EU have the best of both worlds, reputation and innovation, by letting innovative technology, and reputation systems specifically, do the regulatory work? My answer is no. I first take reputation systems seriously by examining how they work and what they may achieve. Reputation systems are based on innovative algorithmic technology and generate trust among strangers. Self-regulation advocates argue that reputation systems are well suited, and in any case better than top down regulatory responses, to help users and society deal with the risks generated by the sharing economy . I then turn to the many and well-established flaws in the design and function of reputation systems. These systems come with clear limitations, and are unable to adequately address the complex regulatory challenges that have followed the sharing economy boom. The EU has to work towards developing innovative regulatory solutions, which allow space for self-regulatory mechanisms but combine them with other regulatory tools. The EU needs to set a "traditional" regulatory framework within which self-regulation can function properly. At the same time rules and regulations should be used to deal with the problems that, by default, cannot be addressed by reputation systems (such as externalities). Such clear cut EU rules must be the outcome of democratic debate.
Keywords: 320; regulation; self-regulation; platform regulation; EU policy challengers; EU responses to technological innovation; sharing economy; European Single Market strategy; technology enabled regulation; consumer protection; European consumer protection law; reputation systems; ratings; consumer harm; Airbnb; Uber; behavioral economics; digital discrimination; reporting bias; European Union law